2013
DOI: 10.1038/labinvest.2012.143
|View full text |Cite|
|
Sign up to set email alerts
|

Adenosine A2B receptor-mediated VEGF induction promotes diabetic glomerulopathy

Abstract: Diabetic nephropathy ranks as the most devastating kidney disease worldwide. It characterizes in the early onset by glomerular hypertrophy, hyperfiltration and mesangial expansion. Experimental models show that overproduction of vascular endothelial growth factor (VEGF) is a pathogenic condition for podocytopathy; however the mechanisms that regulate this growth factor induction are not clearly identified. We determined that the adenosine A 2B receptor (A 2B AR) mediates VEGF overproduction in ex vivo glomerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 48 publications
4
45
0
Order By: Relevance
“…61 The functional role of Adora2b signaling on VEGF release has been controversial, with some studies showing VEGF promotion and other studies showing VEGF reduction. 62,63 To our knowledge, the present studies provide the first genetic evidence for a functional role of Adora2b signaling in attenuating renal VEGF levels. Indeed, we found that renal VEGF expression was markedly increased in Adora2b gene-targeted mice after 16 weeks of diabetes compared with wild-type mice.…”
Section: Discussionmentioning
confidence: 61%
“…61 The functional role of Adora2b signaling on VEGF release has been controversial, with some studies showing VEGF promotion and other studies showing VEGF reduction. 62,63 To our knowledge, the present studies provide the first genetic evidence for a functional role of Adora2b signaling in attenuating renal VEGF levels. Indeed, we found that renal VEGF expression was markedly increased in Adora2b gene-targeted mice after 16 weeks of diabetes compared with wild-type mice.…”
Section: Discussionmentioning
confidence: 61%
“…The association of adenosine and VEGF secretion dependent on A 2A or A 2B AR is also documented in multiple studies. 20,21 In this study, we found that A 2B rather than A 2A AR is implicated in the adenosine and NECA elicited upregulation of VEGF, based on the observation that an A 2A AR agonist CPA exerted a negligible effect on the expression of VEGF. In addition, A 2B has been observed to be preferentially expressed in human microvascular endothelial cells.…”
Section: Discussionmentioning
confidence: 67%
“…Results obtained are comparable to the earlier in-vivo and in-vitro studies. 18,19 The differential expression of adenosine receptor was first described by Pawelczyk et al 20 The alteration turns off the inhibition on VEGF-A release accompanied by an increase in the production of this growth factor release in diabetic state.…”
Section: Discussionmentioning
confidence: 99%